2019
DOI: 10.1002/ppul.24430
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic growth deficiency in childhood cancer survivors may cause overestimation of lung disease

Abstract: Introduction Survivors of childhood cancers undergo routine pulmonary function testing as they are at an increased lifetime risk for significant lung disease. However, this population also demonstrates growth abnormalities that could influence the interpretation of these tests, as reference equations are based on standing height. We aim to determine the impact of the relative thoracic growth deficiency in childhood cancer survivors on the interpretation of pulmonary function testing. Methods Standing height an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…There was significant difficulty in finding suitable organs, given that the chest wall was the size of a 4-year-old when the patient was 17 years of age. 21 In this cohort, 10/39 (25%) of the patients were symptomatic; symptoms were consistent with either obstructive lung disease or restrictive/interstitial lung disease. Not all of these symptoms correlated with abnormal PFTs.…”
Section: -22 Yearsmentioning
confidence: 76%
“…There was significant difficulty in finding suitable organs, given that the chest wall was the size of a 4-year-old when the patient was 17 years of age. 21 In this cohort, 10/39 (25%) of the patients were symptomatic; symptoms were consistent with either obstructive lung disease or restrictive/interstitial lung disease. Not all of these symptoms correlated with abnormal PFTs.…”
Section: -22 Yearsmentioning
confidence: 76%
“…Childhood cancer survivors (CCS) have thoracic growth deficiency, which disproportionately affects their upper segment length (USL) compared with children without cancer. Dean et al 13 hypothesized that CCS have a disparity in the ratio of USL to standing height that leads to overestimation of PFT abnormalities. To test this hypothesis, they compared PFT results in CCS to age‐matched historical standards and also used double the USL as an alternative for standing height in calculation of predicted PFT values.…”
Section: Spirometry Based Studiesmentioning
confidence: 99%
“…Impaired pulmonary function in childhood cancer survivors (CCS) is associated with decreased physical function; restrictive defects and D L CO are the most commonly observed pattern 47–49 . Growth abnormalities also may occur among CCS, 50,51 leading Dean et al 52 to hypothesize that impaired thoracic growth may play a role in PFT abnormalities observed among this population. They found that 107 CCS were shorter on average than historical controls, with disproportionate shortening of the upper body segment—the distance from the top of the head to the end of the coccyx.…”
Section: Introductionmentioning
confidence: 99%